SEC suffers three recent losses despite increased focus on trial readiness. Issue 1 (27th February 2014) - Bettigole, Bruce; Kelly, Katherine; Kruly, Charlie
Abstract : Purpose: – To contrast SEC Chair Mary Jo White's enforcement rhetoric with the results of recent SEC enforcement actions. Design/methodology/approach: – Discusses a speech in which White explained the benefits she believes result from taking cases to trial. Proceeds to review three recent cases in which the Commission has lost after a jury trial or summary judgment motion. Findings: – Based on three recent SEC losses, White may be correct in her prediction that trials promote "public accountability for both defendants and the government." Practical implications: – Some defendants in SEC enforcement actions may ultimately prevail if they refuse to settle with the Commission. Originality/value: – This article analyzes the early results of the SEC's newly-announced enforcement policies.